Crescimento inicial de cultivares de cafeeiro com diferentes doses de nitrogênio, fósforo e potássio - Vilela, Diego Júnior Martins; Carvalho, Gladyston Rodrigues; Botelho, Cesar Elias; de Carvalho, Alex Mendonça [UNESP]; Praxedes, Marina Angélico; Santos, Milena Christy; Fernandes, Fernando Costa (Coffee Science, 2017)
The mineral nutrition of the coffee tree is very important for its yield, and several places that previously were considered unfit for the cultivation, today exhibit highly productive crops, where soil fertility correction, over time, combined with proper mineral nutrition, are some of the main factors for this success. The aim of this research was to evaluate four new coffee cultivars at initial growth under different doses of nitrogen, phosphorus and potassium. The trial was carried out at the Experimental Farm of EPAMIG, in São Sebastião do Paraíso, MG, Brazil, on February 2012. Four cultivars were used in twelve treatments (factorial scheme, four cultivars, three nutrients and four doses), under randomized block design. Joint analysis of the data was made. The traits evaluated were: height, diameter of the stem, growth of the first plagiotropic branch, number of plagiotropic branches, chlorophyll index and soil and leaf analyzes. It was concluded that in the initial chemical conditions of the soil used in the experiment, fertilizations with N, P and K, both in cover fertilization and first-year fertilization, can be reduced in up to 50% in coffee plantations of the cultivars Pau Brasil MG1, Paraíso MG H419-1 and Topázio MG 1190.
Initial growth of coffee tree cultivars with different doses of nitrogen, phosphorus and potassium
Keywords: Coffea arabica; Mineral nutrition; Plant breeding